Violence symbolique et citoyenneté littéraire. La nomophatique dans le champ argentin - Thérèse Courau (Caravelle)
Based on the example of the Argentinian literary field, this paper intends to explore how masculinism operates in discourses and institutional practices that have historically served the marginalization of women outside the canon. We will consider this process as an expression of the symbolic violence which includes the exclusion of women from literary citizenship.